Economics of copra production in selected barangays of Buenavista, Guimaras - Aranda, Odessa Turija
This paper provides a background and baseline information on the prevailing profile of copra production and profitability with the use of thirty-five producers based in Buenavista, Guimaras. This study also gave an overview on the problems encountered by copra producers and provided recommendations for the improvement of the local copra industry., Costs and returns analysis showed that average costs in copra production was P9.14/kg. Of the average costs, average fixed costs, average variable costs, and opportunity costs accounted for .33, 26.59, and 73.08 , respectively. Average fixed costs was P.03/kg where a third (33.33 ) can be attributed to depreciation costs (P.02/kg). As to the average variable costs of the respondents, P2.43/kg was incurred which was primarily attributed by cost of hired labor (89.71). Opportunity costs/kg for all producers was P6.68. The major opportunity costs (81.44) was the implicit cost of coconuts. Average revenue was P9.43/kg. As a whole, the respondents gained P6.97/kg financial profit. Meanwhile, gross profit was P7.00 for all respondents. Copra producers in Buenavista, Guimaras earned a positive P0.29/kg economic profit.